1994
DOI: 10.1182/blood.v84.8.2741.2741
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of rat peripheral polymorphonuclear leukocyte response by nitric oxide and arginine

Abstract: The effect of nitric oxide (NO) on the luminol-dependent chemiluminescence (LCL) response of rat polymorphonuclear leukocytes (PMNLs) was analyzed by using sodium nitroprusside (SNP), a NO donor, and L-arginine (L-arg), a NO precursor. A significant reduction in the LCL intensity was observed in presence of SNP (100 mumol/L) or L-arg (5 or 10 mmol/L) in arachidonic acid (AA) phorbol ester (PMA) and formyl- methionyl-leucyl-phenylalanine stimulated PMNLs. However, opsonized zymosan-induced LCL was not attenuate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Such an observation has not been published previously and indicates that these agents should be used with caution to delineate the role of NO in PMNLs free radical generation estimated by luminol. In our previous study, while investigating the role of endogenous as well as exogenous NO on rat PMNLs free radical generation, we observed that NO from both sources inhibited, as well as scavenged, the free radicals (Seth et al, 1994). Similar observations were also obtained by others in human PMNLs (Rubanyi et al, 1991;Clancy et al, 1992).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Such an observation has not been published previously and indicates that these agents should be used with caution to delineate the role of NO in PMNLs free radical generation estimated by luminol. In our previous study, while investigating the role of endogenous as well as exogenous NO on rat PMNLs free radical generation, we observed that NO from both sources inhibited, as well as scavenged, the free radicals (Seth et al, 1994). Similar observations were also obtained by others in human PMNLs (Rubanyi et al, 1991;Clancy et al, 1992).…”
Section: Discussionsupporting
confidence: 84%
“…by use of a dual channel lumiaggregometer (Model 560 Chronolog Corp. Havertown, PA, U.S.A.) and has been presented as LCL and LUCDCL units. The LCL or LUCDCL units have been defined as the maximum output (obtained from stimulated PMNLs) divided by the 'gain setting' of the instrument at the time of response (Seth et al, 1994). The assay mixture (1000 pl) contained 1-5 x 106 PMNLs, 10 giM luminol or 50 gM of lucigenin, test substance (L-and D-arginine analogues) and FMLP (1 x 10-6 M) or AA (1 x I0-5 M).…”
Section: Isolation Of Pmnlsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to ROS scavenging, NO attenuated NADPH oxidase activity [5] and inhibited ROS generation, and a NO-dependent increase in the intracellular calcium augmented ROS generation [4]. NO-mediated modulation of ROS generation has also been demonstrated in the conditions associated with the increased accumulation of NO, such as hypoxia-reoxygenation [1,4,6] and lipopolysaccharide treatment [7].…”
Section: Introductionmentioning
confidence: 99%